Evaluation of Three-Dimensional Heads up Ophthalmic Surgery Demonstration From the Perspective of Surgeons and Postgraduate Trainees. Issue 7 (October 2021) - Cheng, Teck Chee; Yahya, Maliha Farah Nurhazirah; Mohd Naffi, Ainal Adlin; Othman, Othmaliza; Seng Fai, Tang; Yong, Meng Hsien; Wan Abdul Halim, Wan Haslina; Mustapha, Mushawiahti; Che Hamzah, Jemaima; Md Din, Norshamsiah; Bastion, Mae-Lynn Catherine
Abstract : Background: To evaluate the satisfaction of surgeons and trainees with three-dimensional (3D) ophthalmic surgery during a demonstration compared to traditional surgery Methods: This validated questionnaire-based study was conducted over 1-month during which Ngenuity 3D surgery was demonstrated. All surgeons and trainees exposed were recruited to complete a questionnaire comprising visualization, physical, ease of use, teaching and learning, and overall satisfaction. Results: All 7 surgeons and 33 postgraduate students responded. Surgeons reported no significant difference except overall ( P  = 0.047, paired t -test). Postgraduate trainees reported significantly better experience with 3D for illumination ( P  = 0.008), manoeuvrability ( P  = 0.01), glare ( P  = 0.037), eye strain ( P  = 0.008), neck and upper back strain ( P  = 0.000), lower back pain ( P  = 0.019), communication ( P  = 0.002), comfortable environment ( P  = 0.001), sharing of knowledge ( P  = 0.000), and overall ( P  = 0.009). Conclusions: During early experience, surgeons and trainees reported better satisfaction with 3D overall. Trainees had better satisfaction with 3D in various subcomponents of visualization, physical, ease of use, and education. Abstract : Supplemental Digital Content is available in the text